Musical lives: Portraits of composers in biographical novels - Stępień-Kutera, Kamila (Chopin Review, 2023)
The biographical novel, currently so popular among readers and authors alike, only recently acquired its status as an emerging literary genre: the process of its separation from the historical novel as more broadly conceived can be dated to the second half of the twentieth century. It is also worth remembering that the biography itself, as one of the types of scholarly text belonging to the field of history, only became the subject of more serious theoretical considerations during the first decades of the twentieth century. The biographical novel, combining – in various ways – historical reality with the author’s creativity, affords a unique opportunity to get inside the lives of its protagonists. Relatively few of the most outstanding works in the genre are devoted to composers, but a number of them open up fascinating vistas for study. In my reading of Thomas Mann’s Doctor Faustus, Julian Barnes’s The Noise of Time, Josef Škvorecký’s Scherzo capriccioso. Veselý sen o Dvořákovi and Jean Echenoz’s Ravel, I endeavour to show how the authors build a credible image of their characters. The present study forms an anacrusis to further reflection.